Paleontology, stratigraphy and historical geology problems in M.V. Lomonosov work «About Earth’s layers» - V. N. Komarov (Известия высших учебных заведений: Геология и разведка)
The 250th anniversary of death of generous Russian scientist M.V. Lomonosov is celebrated in April 2015. His work «About the Earth’s layers» is the most important geological work of Lomonosov, which ideas were ahead of time and concerned different aspects of paleontological investigations. The stratigraphic investigations showed the stratification of geological sections. The idea of consistente volution of the nature played an important role for natural sciencesis.